THE SHANGHAI COOPERATION ORGANIZATION - BOOK REVIEW - Kamaruddin, Saslina; Ikhsan, Muhammad Izwan (International Journal of Law in Changing World, 2022)
The Shanghai Cooperation Organization (SCO) is a significant international gathering. The SCO, which was founded in June 2001, has grown to become the world's largest and most populous regional cooperation organisation, encompassing three-fifths of the Eurasian continent. The Shanghai Cooperation Organization (SCO) book reflects and demonstrates the SCO's mission as a political, economic, and security entity in Eurasia. The book's goal and structure demonstrate that SCO topics are explored dynamically: what the SCO was when it was created, what it is now and how it works, and what its future potentials are. The book compares the SCO's initial and current levels of interaction and cooperation and suggests new goals and tasks. Prospects and frontiers have been explored because of such an examination. SCO is distinguished from Eurocentric regionalism in the books. A comparative legal study, comparative regionalism, a comparative historical approach, social science methodologies, a multidisciplinary approach, legal analysis, empirical observation, statistical and economic data, and expert assessments were used in this book. The writers of the book have also examined the range of SCO states, examine the Organization's legal opportunities and problems. Including of the bloc's economic, humanitarian, legal, trade, labour, migratory, and environmental cooperation opportunities, as well as its security and defence problems There are three sections in this book. The first, "Building a Basis: Roots and Grounds," provides an overview of the Organization's initial foundations and characteristics. The authors also assess these foundations in terms of development and prospects. Chapter 2 discusses the SCO's organizational and legal foundations, its institutional development over the past 20 years, and whether the current structure and core values ensure future growth. In Chapter 3, the authors examine the SCO's international legal framework, highlight new forms and methods of cooperation, and argue for its declaratory nature. The fourth chapter seeks SCO and security cooperation. The authors investigate the process of shifting the SCO's security agenda from conventional to non-military issues and conclude that the "Asian" model of regional security is increasingly being adopted in the "Greater Asian" environment. Chapter 5 provides a comprehensive and critical international legal analysis of the normative and conceptual framework, as well as SCO mechanisms, in combating extremism to obtain scientifically based new knowledge on the subject, thereby contributing to the development of effective global, regional, and national coordination. Part II, "Moving Through the Levels of Cooperation," investigates some promising areas of organisational development. Human rights focus on Chapter 6, which examines the likely convergence of legal values and attitudes in SCO countries and Western Europe. The authors advocate the Eurasian concept of human rights to broaden horizons and balance human societies. The seventh chapter focuses on SCO humanitarian cooperation. The study identifies the primary barriers to humanitarian collaboration, intercultural dialogue, and educational space development. Chapter 8 discusses the SCO countries' labour policies and their potential for convergence as a new world order. Discover the rationale for expanding commercial ties and, eventually, legal harmonisation. Discover the rationale for expanding commercial ties and, eventually, legal harmonisation. Chapter 9 investigates labour migration among SCO member countries. The SCO is not currently focusing on migrants' social and labour rights. This chapter identifies key challenges and demonstrates how to strengthen collaboration. The goal of Chapter 10 is to identify the most promising areas of collaboration between the SCO and the EAEU to learn how to expand and strengthen their engagement. Part III of the book focuses on New Prospects and Horizons, highlighting untapped SCO prospects and new growth horizons. The primary goal is to strengthen economic cooperation. The economic requirements for SCO economies to grow are examined in Chapter 11. It identifies factors impeding interregional trade and economic cooperation. The authors investigate economic interaction priorities as well as legal and regulatory evolution. The discussion of energy cooperation continues in Chapter 12. The SCO has promoted it successfully. However, the SCO's energy cooperation faces challenges. Legal methods are being considered for strengthening. The authors discuss the economic cooperation of SCO countries in constructing new transportation and communication channels in Chapter 13. According to them, integrating the EAEU and SREB on the SCO platform could result in a new economic cooperation model in the "Russia-China-CA" triangle. The 14th chapter discusses India's SCO membership options. The authors argue that re-contextualizing the Organization could hasten regional economic development by bringing in new partners. Concerns are examined by looking at the region's economy. The final chapter investigates the prospects and opportunities for environmental cooperation. This shift in SCO collaboration began only recently. Prospects are provided in the report based on the importance of preventing climate change, maintaining the ecological balance in the SCO space, and restoring biodiversity for future generations, thereby creating favourable conditions for sustainable development. Throughout the reading, every chapter of the book shows challenges in the respective field, poses conclusions, and suggests new cooperation prospects. Nevertheless, the book provides a valuable and absorbing window into the Shanghai Cooperation Organization (SCO) is one of the fastest-growing multipolar centres, covering China, India, Russia, and southern Eurasian countries, and how the SCO's operations have evolved beyond its initial focus on security and stability to include cooperation with the UN, G20, BRICS, NATO, and ASEAN. As a conclusion to the volume's collective research, the authors have allowed for remarks and general suggestions. It is intended that the book would feed researchers' study and give decision-makers important SCO development proposals.